Seroprevalence of dengue virus infection among the patients admitted with acute febrile illness in a tertiary care hospital in Central India - P. S., Pooja; Kokate, Sandeep B.; Shrikhande, Sunanda (International Journal Of Community Medicine And Public Health, 2025)
Background: Dengue is the most rapidly spreading mosquito-borne viral disease in tropical and subtropical regions, posing a major public health challenge. Seroprevalence studies are vital for understanding its burden and guiding control strategies. Methods: This cross-sectional study was conducted in the Department of Microbiology at Government Medical College, Nagpur, from July 2022 to June 2024. A total of 7814 patients admitted with acute febrile illness (AFI) were screened, and 429 clinically suspected dengue cases were selected. Serum samples were tested for Dengue NS1 antigen, IgM, and IgG antibodies using enzyme-linked immunosorbent assay (ELISA). Results: Out of 429 suspected cases, 109 were confirmed positive for dengue, yielding a seroprevalence of 25.41%. The highest incidence was observed in the 21–30 years age group (23.86%), with females (54.13%) being more affected than males. A majority of cases (74.31%) were from urban areas. Peak incidence occurred during the monsoon months, particularly in September. Conclusions: The study highlights a significant seroprevalence of dengue in Central India, emphasizing the need for vigilant surveillance, timely diagnosis, and effective vector control measures, especially during the monsoon season.